Establishment of scientific research in communication studies in the 1920s - 1930s - Denis Kislov (Історія науки і техніки, 2019)
The article discusses and analyzes the role assessment and communication significance in state control systems in works and prominent representatives’ statements of political thought from antiquity to the beginning of the twentieth century in accordance with the understanding of this phenomenon essence in the considered historical epochs. It is shown that from the history of political thought, although some well-founded concepts of the relationship between the authorities and the population of the thinkers of ancient China, India, and antiquity are known, they require more detailed and systematic understanding. The influence of the managerial and communicative ideas of Confucius, Plato and Aristotle on the subsequent works of Caesar, Cicero, the thinkers of the Middle Ages, the Renaissance and the Enlightenment are consistently discussed. A comparative analysis of individual views on the relationship between the state of public administration and communication of theologians and scientists of the XIII-XVIII centuries was conducted: F. Aquinas, F. Petrarch, L. Bruni, N. Machiavelli, M. Luther, T. More, T. Campanella, J. Boden, G. Grotius, J. Locke, T. Hobbes. Particular attention is paid to the ideas of S. Montesquieu, I. Kant, and G.-V.-F. Hegel as the founders of the scientific discourse around the problems of war and peace, the effectiveness of government and relations with the subjects of this management, with the people. In particular, the developments of the Chicago school in the United States and the Institute for Social Research in Germany, which laid the theoretical foundation for the beginning of the formation of information and communication theories that created the basis of the modern stage of communication development in the late twentieth century - early twenty-first century. Research and analysis in the work of the first historical ideas and theoretical concepts of the role, communication place and importance in public administration systems, advanced for 2500 years by a galaxy of eminent thinkers of the past, allows to rethink the sources of conceptual ideas of communicology put forward in the 20th century and approach the objective assessment of the perspective the role of the communication component of the humanity civilizational development in the twenty-first century.